Staging and Pretensioning of Cable-Stayed Bridges. (February 2019) - Modano, M; Mascolo, I; Fraternali, F
Abstract: This paper describes a study of cable-stayed bridges (CSBs), with a focus on the computation of the optimal pre-tensioning cable forces to be applied in the construction phase and the service behavior. We distinguish the case of a structure built using temporary supports from that of a structure built through the so-called cantilever method. We formulate an optimization procedure aimed at determining the cable pre-tensioning forces that ensure a target stress distribution along the longitudinal axis of the structure. The goal of this procedure is to make the bending diagram distribution as much uniform as possible over the bridge length, in order to avoid undesired stress localization effects. The proposed procedure is based on an influence matrix approach, and makes use of a single pre-tensioning cycle. It can be applied to optimize the mechanical response of the structure in any phase of its life cycle.